Analysis of the Results of Physical Training for Elementary School Students at the 50th Elementary School in Quwa County, Fargo. (Eurasian Journal of Learning and Academic Teaching, 2023)
The 50th elementary school in Quwa County reported on the results of pedagogical and scientific research using special mathematical and statistical methods